Moderating effects of body composition biomarkers on the relationship between thyroid hormones and cognitive performance in euthyroid older adults: insights from NHANES data - Li, Xiaosong; Duan, Hongliang; Liu, Shuang; Li, Hanyang; Zhang, Hong (Frontiers in Endocrinology, 2024)
Thyroid hormones are crucial for cognitive function and can influence cognitive performance even in euthyroid individuals. This study aims to analyze how thyroid hormones affect cognitive performance in the elderly, and whether body composition biomarkers moderate this relationship. The goal is to determine whether lifestyle interventions should focus on weight loss, overall body fat reduction, or abdominal fat loss. We conducted an analysis of data from the NHANES 2011-2012, focusing on thyroid hormone levels, cognitive performance, and body composition metrics in euthyroid individuals aged 60 to 80 years. Statistical analyses were performed using R Studio and Stata, employing methods such as Pearson correlation, ordinal logistic regression, and linear regression analysis. Thyroid hormones were significantly associated with short-term memory, delayed memory, and executive function, but not with working memory. Specifically: 1) Immediate memory was linked to total triiodothyronine (TT3), Jostel’s TSH index (TSHI), and Thyroid Feedback Quantile-based Index (TFQI); 2) Delayed memory was associated with free triiodothyronine (FT3), TT3, and TSHI; 3) Executive function correlated with free thyroxine (FT4), FT3/FT4 ratio, TSHI, and TFQI. Moreover, Body weight moderated the relationship between thyroid hormones and delayed memory, and both body weight and waist circumference influenced short-term memory. No moderating effect of body composition was observed for executive function. Thyroid hormones are associated with short-term memory, delayed memory and executive function, with body composition moderating these relationships for memory but not for executive function. These findings suggest that interventions should prioritize weight and abdominal fat loss to improve cognitive outcomes.